Biochemical assessment of patients following ketogenic diets for epilepsy: Current practice in the UK and Ireland. Issue 1 (29th November 2019) - Schoeler, Natasha E.; Simpson, Zoe; Whiteley, Victoria J.; Nguyen, Patty; Meskell, Rachel; Lightfoot, Kathyrn; Martin‐McGill, Kirsty J.; Olpin, Simon; Ivison, Fiona; ,
Abstract: Objective: Biochemical assessment is recommended for patients prior to initiating and following a ketogenic diet (KD). There is no published literature regarding current practice in the UK and Ireland. We aimed to explore practice in comparison with international guidelines, determine approximate costs of biochemical testing in KD patients across the UK and Ireland, and promote greater consistency in KD services nationally. Methods: A survey was designed to determine the biochemical tests requested for patients at baseline, 3, 6, 12, 18, and 24 months + on KD. The survey was circulated to 39 centers across the UK and Ireland. Results: Sixteen centers completed the survey. Full blood count, electrolytes, calcium, liver function tests (LFTs), lipid profile, and vitamin D were requested at all centers at baseline, in keeping with international guidelines. Bicarbonate, total protein, and urinalysis were less consistently requested. Magnesium and zinc were requested by all centers, despite not being specifically recommended for pre‐diet evaluation in guidelines. Urea and electrolyte profiles and some LFTs were consistently requested at follow‐up, in accordance with guidelines. Other LFTs and renal tests, full blood count, lipid profile, acylcarnitine profile, selenium, vitamin D, and urinalysis were less consistently requested at follow‐up. The mean costs of the lowest and highest number of tests requested at baseline in our participating centers were £167.54 and £501.93; the mean costs of the lowest and highest number of tests requested at 3‐month follow‐up were £19.17 and £450.06. Significance: Biochemical monitoring of KD patients varies widely across the UK and Ireland and does not fully correspond to international best practice guidelines. With an ongoing drive for cost‐effectiveness within health care, further work is needed to streamline practice while ensuring patient safety.